What is the care economy? A scoping review on current evidence, challenges, facilitators and future opportunities - Blackberry, I.; Boak, J.; Barclay, K.; Khalil, H. (Frontiers in Public Health, 2025)
BackgroundThe care economy gained its prominence during the COVID-19 pandemic. The value and impact of caregiving, mostly shouldered by women, was not as visible until such crisis point. Health care and social support sectors represent the largest and fastest growing industry globally. This scoping review aims to elucidate the current state of play in the care economy, where there is a great reliance on informal and formal care workforce to deliver care for populations across all age groups and abilities.MethodsFollowing Joanna Briggs Institute (JBI) methodology and PRISMA-SCR reporting guidance, we searched MEDLINE, Embase, CINAHL, PsycINFO, Campbell collaboration database, Social Science Abstracts, Library and Information Science Abstracts (LISA) and Scopus. Quantitative and qualitative original research on disability, aged care, early childhood education and care, rural, veterans, migrants and informal and formal care workforce from January 2018 until November 2023 were examined.ResultsOf 354 studies selected, 20% were from the United States of America, 11% each were from China and the United Kingdom. Most studies employed cross-sectional design. A quarter of the studies included adults aged 65 years and above while 6% were adults aged 18 to 64 years. These age groups combined were included in an additional 27% of studies. Women were overrepresented in 70% of the studies. Nearly two-thirds of caregivers were spouses or partners. Barriers to providing care were lack of education, support and monitoring of caregiver well-being, loss of income or ability to earn money, reduced social life and increased out-of-pocket costs. Gaps in research included migrant populations’ contribution to the care economy, gender and diversity inequality in the care economy. The care economy could be improved through providing education for caregivers, care workforce engaging with caregivers in the care plan, and governments’ overhaul of compensation for caregivers through direct financial support and employment benefits.ConclusionThe care economy is an emerging research area. There continues to be a paucity of research evidence across some geographical areas. Studies are mostly short term or small scale with very little evidence around the value of care. Given the growing aging population, more research is needed to elucidate the positive aspects of caring by formal and informal care workforce to the population, society and economy.Protocol registrationThe protocol is registered with Open Science Framework (10.17605). “Definitions, key themes and aspects of the care economy-a scoping review protocol,” https://osf.io/ypmuh.